Force-induced growth of adhesion domains is controlled by receptor mobility - Smith, Ana-Suncana; Sengupta, Kheya; Goennenwein, Stefanie; Seifert, Udo; Sackmann, Erich (Proceedings of the National Academy of Sciences of the United States of America, 2008)
In living cells, adhesion structures have the astonishing ability to grow and strengthen under force. Despite the rising evidence of the importance of this phenomenon, little is known about the underlying mechanism. Here, we show that force-induced adhesion-strengthening can occur purely because of the thermodynamic response to the elastic deformation of the membrane, even in the absence of the actively regulated cytoskeleton of the cell, which was hitherto deemed necessary. We impose pN-forces on two fluid membranes, locally pre-adhered by RGD-integrin binding. One of the binding partners is always mobile whereas the mobility of the other can be switched on or off. immediate passive strengthening of adhesion structures occurs in both cases. When both binding partners are mobile, strengthening is aided by lateral movement of intact bonds as a transient response to force-induced membrane-deformation. By extending our microinterferometric technique to the suboptical regime, we show that the adhesion, as well as the resistance to force-induced de-adhesion, is greatly enhanced when both, rather than only one, of the binding partners are mobile. We formulate a theory that explains our observations by linking the macroscopic shape deformation with the microscopic formation of bonds, which further elucidates the importance of receptor mobility. We propose this fast passive response to be the first-recognition that triggers signaling events leading to mechanosensing in living cells.
Keywords: cell adhesion under force; dynamic reflection interference contrast microscopy; magnetic tweezers; mobile integrin-RGD bonds; model systems